“I needed to remind myself never to go back to that dark of a place:” queer community members in the Flint Hills region of Kansas communicating challenges of/with mental health through body art and non-surgical body modifications - Mattson, Jacquelyn Ann (Kansas State University, 2019)
This thesis explores experiences of mental health among some queer community members in the Flint Hills region of Kansas. This research specifically investigates how the queer community in the Flint Hills region of Kansas, i.e. anyone who identifies with a marginalized sexuality and/or gender identity, communicates their experiences with mental health through their pieces of body art and/or non-surgical body modifications, which are defined as tattoos, piercings, scarification, and intentional branding, to themselves and others. The Flint Hills region of Kansas is defined as the cities of Manhattan, Junction City, Fort Riley, Riley, Wamego, Ogden, and Abilene. Centered within multiple theoretical frameworks from critical and communication studies disciplines, this thesis examines the stories and experiences behind the imagery and adaptations to some of the queer bodies, in this specific location, as it communicates experiences with mental health. Body art/non-surgical body modifications are a road map to the traumas we have experienced; the scars show our resilience. Those who assist with this research vary in ages (from 18-46), marginalized sexualities (gay, lesbian, bisexual, pansexual, and queer), marginalized gender identities (transgender, gender non-binary, gender queer, and androgynous), and racial identities/ethnicities (white, Black, Hispanic, Native/indigenous, and mixed race/ethnicities). The experiences and diagnoses with mental health range from depression, anxiety, bipolar disorder, borderline personality disorder, and suicidality/suicidal ideation. Listening to these narratives through in-depth, open-ended questions and natural conversations, and taking photographs of all discussed pieces of body art/non-surgical body modifications it was clear that these pieces serve to communicate both to others and themselves. When communicating to others, it was to memorialize the loss of someone. Five themes surfaced when these individuals were communicating their experiences with mental health to themselves: 1. attempting to gain control of their lives, even if that control is temporary; 2. transgender and gender nonbinary folks transitioning and fighting for space; 3. experiences with and attempts to prevent self-harm and/or self-mutilation; 4. symbolizing failed suicide attempts; and 5. individual engagements with personal mental health diagnoses. The implications of this research ignite and further conversations about mental health among queer individuals in the Flint Hills region of Kansas and strives to reduce the stigma surrounding communicating about experiences with mental health, especially among marginalized communities.
Keywords: queer; tattoos; body art; queer community; LGBT; piercings